Titanium Implants in the Nose: State of the Art - àWengen, Daniel F. (Facial Plastic Surgery, 2022)
Titanium implants in the head have been used widely for decades. Dental implants as well as titanium plates, screws, and mesh have been an integral part of dental and maxillofacial surgery. In the nose, titanium implants were started in 2003. Their purpose is to increase structure and stiffness to nasal cartilages widening the airway. This overview describes the use of titanium implants in the various locations in the nose. We concentrate on three locations: Breathe Implants on the upper lateral cartilage to widen the internal nasal valve, modified breathe implants in the lower lateral nasal wall fixed to the piriform aperture as batten grafts to widen the external nasal valve, and flattened breathe implants as titanium septum plates to straighten and strengthen the nasal septum.
Keywords: rhinoplasty; nasal obstruction; titanium implants; internal nasal valve; external nasal valve